Comparative Analysis of Programming Languages for Developing System User Interfaces - Fesenko, A.; Sotnik, S. (ХНУРЕ, 2026)
The work considers the issue of choosing a programming language for developing a system's user interface. A comparative analysis of the programming languages C++, C#, and Python has been conducted in terms of their suitability for creating interfaces, taking into account the requirements for performance, ease of development, cross-platform compatibility, and the possibility of integration with system components. The main advantages and disadvantages of each language have been identified, and the areas of their appropriate application in developing interfaces for various systems have been outlined. The results obtained can inform a well-informed choice of software development tools. У роботі розглянуто питання вибору мови програмування для розробки користувацького інтерфейсу системи. Проведено порівняльний аналіз мов програмування C++, C# та Python з точки зору їх придатності для створення інтерфейсів, з урахуванням вимог до продуктивності, зручності розробки, кросплатформеності та можливості інтеграції з системними компонентами. Визначено основні переваги та недоліки кожної мови, а також окреслено області їх доцільного застосування при розробці інтерфейсів систем різного призначення. Отримані результати можуть бути використані при обґрунтованому виборі інструментів розробки програмного забезпечення.
Порівняльний аналіз мов програмування для розробки користувацьких інтерфейсів систем
Keywords: user interface; Python; GUI; software systems